2007
DOI: 10.1038/sj.emboj.7601684
|View full text |Cite
|
Sign up to set email alerts
|

XTsh3 is an essential enhancing factor of canonical Wnt signaling in Xenopus axial determination

Abstract: In Xenopus, an asymmetric distribution of Wnt activity that follows cortical rotation in the fertilized egg leads to the dorsal-ventral (DV) axis establishment. However, how a clear DV polarity develops from the initial difference in Wnt activity still remains elusive. We report here that the Teashirt-class Zn-finger factor XTsh3 plays an essential role in dorsal determination by enhancing canonical Wnt signaling. Knockdown of the XTsh3 function causes ventralization in the Xenopus embryo. Both in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 50 publications
(63 reference statements)
2
25
2
Order By: Relevance
“…The presence of multiple copies of this atypical zinc-finger motif is a hallmark of Teashirt family proteins (Manfroid et al, 2004). Smed-Teashirt lacks the basic motif, the homeodomain and the second C-terminal zinc finger found in vertebrate orthologs, which are also lacking in Drosophila Teashirt and the Drosophila Teashirt paralog Tiptop (Onai et al, 2007). The three mouse teashirt genes can rescue the Drosophila teashirt loss-of-function phenotype, suggesting that Teashirt proteins have similar biochemical activities in highly divergent animals (Manfroid et al, 2004).…”
Section: Planarian Teashirtmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of multiple copies of this atypical zinc-finger motif is a hallmark of Teashirt family proteins (Manfroid et al, 2004). Smed-Teashirt lacks the basic motif, the homeodomain and the second C-terminal zinc finger found in vertebrate orthologs, which are also lacking in Drosophila Teashirt and the Drosophila Teashirt paralog Tiptop (Onai et al, 2007). The three mouse teashirt genes can rescue the Drosophila teashirt loss-of-function phenotype, suggesting that Teashirt proteins have similar biochemical activities in highly divergent animals (Manfroid et al, 2004).…”
Section: Planarian Teashirtmentioning
confidence: 99%
“…XTsh3 inhibition causes ventralization, a phenotype also seen following perturbation of β-catenin (Onai et al, 2007). XTsh3 can enhance Wnt signaling activity in a β-catenin-dependent manner (Onai et al, 2007). In both flies and frogs, Teashirt can localize to the nucleus and bind β-catenin, but its exact molecular function remains unclear Onai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsh-related genes (Tshz) have been characterized in vertebrates (Caubit et al, 2000(Caubit et al, , 2008Manfroid et al, 2004;Koebernick et al, 2006;Coré et al, 2007;Onai et al, 2007;Kajiwara et al, 2009;Jenkins et al, 2010); however, their role in the development of the mammalian CNS is poorly understood. We previously reported that teashirt 3 (Tshz3) mutant mice develop to term but fail to breathe and die quickly at birth (Caubit et al, 2008), suggesting that Tshz3 might play a role in the development of the peripheral and/or central control of respiration.…”
Section: Introductionmentioning
confidence: 99%